2020
DOI: 10.1111/jssr.12653
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Religiosity Among Lesbian, Gay, and Bisexual Emerging Adults

Abstract: Highly religious Americans are relatively likely to oppose lesbian, gay, and bisexual (LGB) rights and many churches are unwelcoming to sexual minorities, which may lead LGB Americans to retreat from religion. To assess this possibility, we investigate trajectories of religious change for sexual minorities and other emerging adults. We use two longitudinal data sources (National Longitudinal Study of Adolescent to Adult Health and the National Study of Youth and Religion) to explore how sexuality predicts the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 58 publications
2
22
2
Order By: Relevance
“…Extant research has found racial/ethnic identity (Grov et al 2006), gender (Savin-Williams andDiamond 2000), and educational attainment/access (Pearson and Wilkinson 2017) shape when an LGB individual personally realizes their sexual identity and when they choose to disclose this identity to another person (Haltom and Ratcliff 2020). Notwithstanding existing empirical insights (see Burge [2018] and Woodell and Schwadel [2020]), there remains a dearth of research examining the effect religion has on sexual minority experiences, particularly coming out. While scholars have theorized how certain religious contexts-particularly evangelical (or "sectarian") Protestantism-lead to conflict between one's religious and sexual minority identity (Page, Lindahl, and Malik 2013;Schwartz and Lindley 2009;Wetzel 2014), the consequences of such conflict remain understudied.…”
Section: Coming Out Of the Closetmentioning
confidence: 99%
See 4 more Smart Citations
“…Extant research has found racial/ethnic identity (Grov et al 2006), gender (Savin-Williams andDiamond 2000), and educational attainment/access (Pearson and Wilkinson 2017) shape when an LGB individual personally realizes their sexual identity and when they choose to disclose this identity to another person (Haltom and Ratcliff 2020). Notwithstanding existing empirical insights (see Burge [2018] and Woodell and Schwadel [2020]), there remains a dearth of research examining the effect religion has on sexual minority experiences, particularly coming out. While scholars have theorized how certain religious contexts-particularly evangelical (or "sectarian") Protestantism-lead to conflict between one's religious and sexual minority identity (Page, Lindahl, and Malik 2013;Schwartz and Lindley 2009;Wetzel 2014), the consequences of such conflict remain understudied.…”
Section: Coming Out Of the Closetmentioning
confidence: 99%
“…LGB individuals have a variety of religious identities (albeit with different rates compared to the overall U.S. population) (Pew Research Center 2013Woodell, Kazyak, and Compton 2015). However, LGB individuals who subscribe or are regularly exposed to more conservative religious ideologies (particularly evangelical Protestantism) may experience internal conflicts when reconciling two seemingly divergent identities (Burge 2018;Woodell and Schwadel 2020).…”
Section: Religion and (Homo)sexualitymentioning
confidence: 99%
See 3 more Smart Citations